ChemInform Abstract: Visible‐Light‐Promoted Conversion of Alkyl Benzyl Ether to Alkyl Ester or Alcohol via O‐α‐sp3 C—H Cleavage. Issue 34 (August 2015) - Lu, Ping; Hou, Tianyuan; Gu, Xiangyong; Li, Pixu
Abstract An iridium‐catalyzed light‐promoted transesterification and debenzylation of alkyl benzyl esters yields alkyl esters and alcohols, respectively.